Prevention of type 2 diabetes mellitus (Herald of the National Children's Medical Center, 2024)
This article discusses the prevention of type 2 diabetes in adults.Materials and methods of research: The search and analysis of publications was carried out using the PubMed and MEDLINE databases, mainly for the last 10 years.Results of the study: There is an increase in diabetes mellitus across the world among different age groups; each country has different climatic and geographic characteristics and dietary traditions. Taking them into account, it is necessary to develop a plan of preventive measures to solve the problem.Conclusion: The prevention of type 2 diabetes requires a comprehensive approach, including healthy eating, increased physical activity, and the management of risk factors such as obesity and stress. The implementation of multifactorial strategies for prevention and treatment helps reduce the incidence of complications and improve patients' quality of life.
Keywords: type 2 diabetes mellitus; prevention; nutrition